2015
DOI: 10.1890/14-0767.1
|View full text |Cite
|
Sign up to set email alerts
|

Connecting differential responses of native and invasive riparian plants to climate change and environmental alteration

Abstract: Abstract. Climate change is predicted to impact river systems in the southeastern United States through alterations of temperature, patterns of precipitation and hydrology. Future climate scenarios for the southeastern United States predict (1) surface water temperatures will warm in concert with air temperature, (2) storm flows will increase and base flows will decrease, and (3) the annual pattern of synchronization between hydroperiod and water temperature will be altered. These alterations are expected to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 92 publications
2
27
0
Order By: Relevance
“…Other authors have suggested changes in the natural succession stages towards more dominant mature-forest and drought-tolerant (Stromberg et al, 2007; Kominoski et al, 2013;Perry et al, 2012;Rivaes et al, 2014). Our results are also supported by Flanagan et al (2015). According to this author the future abundance and cover of native riparian species is driven by hydrology, while invasive species abundance will be more heavily influenced by site-specific factors, such as soil-water contents and nutrients.…”
Section: Alterations In Riparian Connectivity and Complexity Under CLsupporting
confidence: 84%
See 1 more Smart Citation
“…Other authors have suggested changes in the natural succession stages towards more dominant mature-forest and drought-tolerant (Stromberg et al, 2007; Kominoski et al, 2013;Perry et al, 2012;Rivaes et al, 2014). Our results are also supported by Flanagan et al (2015). According to this author the future abundance and cover of native riparian species is driven by hydrology, while invasive species abundance will be more heavily influenced by site-specific factors, such as soil-water contents and nutrients.…”
Section: Alterations In Riparian Connectivity and Complexity Under CLsupporting
confidence: 84%
“…Among the diverse ecosystem services and functions provided by these ecotones, the regulation of river discharges, the filtering of runoff sediments and pollutants from agricultural areas and the regulation of groundwater dynamics are considered critical to an efficient and integrated water resource management (Malanson, 1993;Naiman et al, 2005). Because they represent the interface between freshwater and terrestrial systems, they are highly vulnerable and responsive to climate-change-induced flow regimes and land-use alterations (Camporeale and Ridolfi, 2006;Hoffman and Rohde, 2011;Dufour et al, 2015;Flanagan et al, 2015). Most of the knowledge about the effects of climate-change on these ecosystems comes from the physiological and phenological responses of specific riparian species used as surrogates to assess the systems' vulnerability to climate-driven changes (Rood et al, 2003;Perry et al, 2012;Stromberg, 2001;Stromberg et al, 2010;Singer et al, 2012;RodrĂ­guez-GonzĂĄlez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies under field conditions are important to understand community responses to invasion since these invariably occur against a backdrop of climate-and land use-related changes in flow regime and sediment loading. Such studies offer insights into the relative importance of different drivers in regulating competitive interactions between established native riparian and alien plant species (Flanagan et al 2015), thereby flagging opportunities to influence these interactions through management.…”
Section: Resultsmentioning
confidence: 99%
“…Riparian zones are complex and dynamic habitats noted for their high biodiversity (Naiman and Decamps 1997), yet are threatened by land use and channel management practices, altered hydrology (e.g., abstraction and flow regulation), climate change, and biological invasions (Flanagan et al 2015). Their biodiversity is intimately linked to high spatial and temporal heterogeneity driven by fluvio-geomorphological processes and the potential for waterborne dispersal (hydrochory).…”
Section: Introductionmentioning
confidence: 99%
“…These efforts have led to the recognition of novel ecosystems , directed management funding (Leung et al 2005), and influenced environmental and trade policies (Simberloff 2013). The ways in which invasive species will respond to and interact with future stressors (e.g., coupled climatic and landuse change) are uncertain, yet likely to have substantial repercussions for global economies (e.g., changes in agricultural productivity and input costs) and biodiversity (e.g., changes in species diversity and interactions) Simberloff 2013;Flanagan et al 2015). These effects could be positive and/or negative, depending on the species, social-ecological systems, responses, and locations under consideration.…”
Section: Introductionmentioning
confidence: 99%